THE ROLE OF CULTURE IN THE TRANSLATION PROCESS THROUGH THINK-ALOUD PROTOCOLS - Julia Eka Rini (Linguistik Indonesia, 2014)
Cultural differences have been a major focus in translation. This study investigates two aspects; first, the translation process of culture-bound words and second, the strategies taken by two translators. These translators are English Department students and they have different cultural backgrounds, Moslem Javanese and Buddhist Chinese. Each of them has to translate the same four texts: one text whose cultural background both of them are familiar with, another text whose cultural background both of them are not familiar with and two other texts. Out of the two texts, only one text has a familiar cultural background to one of the translators. The method used to investigate what was happening in the translators’ mind is think-aloud protocols. Two points can be concluded from this study. One, translators’ cultures do play a role in their consideration of choosing the words they use. Two, translators generally use the strategy of cultural substitution if the culture is nearly the same, but they use the strategy of using a neutral word or paraphrasing by related words when the culture is different.